2017
DOI: 10.1108/jefas-02-2017-0042
|View full text |Cite
|
Sign up to set email alerts
|

The valuation performance of mathematically-optimised, equity-based composite multiples

Abstract: Purpose-This paper aims to examine the valuation precision of composite models in each of six key industries in South Africa. The objective is to ascertain whether equity-based composite multiples models produce more accurate equity valuations than optimal equity-based, single-factor multiples models. Design/methodology/approach-This study applied principal component regression and various mathematical optimisation methods to test the valuation precision of equity-based composite multiples models vis-à-vis equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…For example, the study of Clarke (2014) concluded that P/E multiple tend to expand when the interest rates and inflation decrease, and contracts if otherwise. Moreover, multiples that are composite equity-based are found to provide more accurate valuations compared to optimal equity-based single-factor multiples (Nel & Le Roux, 2017). Most of the studies are on selected firms in stock exchanges and appears to be in varied industries.…”
Section: Synthesis Of the Literatures Reviewedmentioning
confidence: 99%
“…For example, the study of Clarke (2014) concluded that P/E multiple tend to expand when the interest rates and inflation decrease, and contracts if otherwise. Moreover, multiples that are composite equity-based are found to provide more accurate valuations compared to optimal equity-based single-factor multiples (Nel & Le Roux, 2017). Most of the studies are on selected firms in stock exchanges and appears to be in varied industries.…”
Section: Synthesis Of the Literatures Reviewedmentioning
confidence: 99%